Dynamic properties of language anxiety - Gregersen, Tammy (Studies in Second Language Learning and Teaching, 2020)
This article begins by examining previous empirical studies to demonstrate that language anxiety, or the negative emotional reaction learners experience when using a second language (MacIntyre & Gardner, 1999), is a dynamic individual difference learner variable. I show that it forms part of an interconnected, constantly-in-flux system that changes unpredictably over multiple time scales. While at certain times this system might settle into an attractor state that accommodates contradictory conditions, perturbations that arise may lead to development and change with the curious possibility that minor disruptions generate large effects while major alterations go unnoticed. In essence, language anxiety (LA) is part of a continuous complex system in which each state evolves from a previous one. After I establish LA as a dynamic variable using the aforementioned criteria, I outline the implications and challenges for researching LA using a dynamic paradigm, which include focusing on individuals, transforming LA research questions, designing interventions and re-thinking data gathering methodologies. I conclude with implications for language teaching that emphasize: 1) raising awareness of the importance of decoding nonverbal behavior to identify moment-by-moment shifts in learner emotion; 2) remaining vigilant concerning variables that are interacting with LA that make this factor part of a cyclical process; 3) understanding that anxiety co-exists with positive emotions to varying degrees and that language tasks are not unanimously enjoyed or universally anxiety-provoking; and 4) incorporating positive psychology activities that proactively encourage buoyancy and resilience for moment-by-moment daily perturbations as well as debilitating disruptions that result in long-lasting influences.